Stropharia populicola (Strophariaceae, Agaricales), a new species from China - Liu, Hong; Mao, Ning; Fan, Li; Guo, Shang (Phytotaxa, 2021)
Stropharia populicola sp. nov., found during autumn under Populus spp. in Shanxi Province of North China, is described and illustrated. Stropharia populicola is similar and closely related to S. jilinensis and S. scabella but can be distinguished from the latter two species by the acanthocytes commonly present in the hymenium. Phylogenetic analysis supports its taxonomic position in the genus Stropharia.